1981
DOI: 10.1111/j.1365-2273.1981.tb01545.x
|View full text |Cite
|
Sign up to set email alerts
|

The anterior commissure of the larynx

Abstract: This study is based on a very large series of histological sections of non-tumour-bearing larynges, most of them in the horizontal plane. Six hundred sections in one larynx were performed to show the constitution of the anterior region of the larynx at all levels. Although the same tissues are present (fibres, glands and vessels) in almost the entire extent of the anterior segment of the larynx, there is a small zone immediately above the vocal cords with neither glands nor vessels. The authors designate this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Clinical appearance of T1a cancer is often in Stage T3 due to its silent infiltration into the thyroid lamina of TC via the Broyles ligament, as the Broyles ligament directly inserts to the intermediate lamina of the TC and the lack of cancer-resistant inner perichondrium facilitates tumor invasion in the AC. [3][4][5] This region is the junction of three levels of the larynx. The AC is a pathway of invasion of the cancer cells into the TC and the three levels of the larynx.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical appearance of T1a cancer is often in Stage T3 due to its silent infiltration into the thyroid lamina of TC via the Broyles ligament, as the Broyles ligament directly inserts to the intermediate lamina of the TC and the lack of cancer-resistant inner perichondrium facilitates tumor invasion in the AC. [3][4][5] This region is the junction of three levels of the larynx. The AC is a pathway of invasion of the cancer cells into the TC and the three levels of the larynx.…”
Section: Discussionmentioning
confidence: 99%
“…[4] The AC is anatomically non-separable unit from the glottis and subglottis. Based on the anatomic and histological studies of the larynx, Andreas and Guerrier [3] reported a small zone in the AC which they called O plan. This zone is deficient in vessels and glands, thereby, facilitating the oncological separation of the AC from the petiole of the supraglottis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This tendinous insertion at first provides a barrier to tumor invasion anteriorly [8], but if the tendon is invaded by tumor, it provides a route for tumor extension anteriorly [8]. Below the anterior commissure, Guerrier’s “plane zero” is devoid of perichondrium and allows direct tumor infiltration of the cartilage [9]. Hence, the anterior commissure is a key structure for tumor spread, it enables tumor spread to different spaces: preepiglottic, paraglottic and subglottic spaces or externally via the vascularized ossification centers of the thyroid cartilage.…”
Section: Larynxmentioning
confidence: 99%
“…20,21,22 Majority of the studies focus on the weak points through which tumours affecting the anterior comissure can extend into other levels of the larynx (supraglottis, subglottis), cartilage or extralaryngeal structures. 23,24,25,26 Clinical evaluation of the lesion depending on whether it has an infiltrating or non-infiltrating morphology implies different behaviour. In case of non infiltrating morphology, the tumour is usually limited to the glottic plane, and in tumours with infiltrating morphology the tumour is often deeply invasive, reaching other planes of the larynx and behaving as a true anterior transglottic tumour.…”
Section: The Anterior Cmmissurementioning
confidence: 99%